Conductive polymer composites from plasticized polylactic acid/carbon black - Buys, Yose Fachmi; Mohd Lazim, Nurul Hakimah (2015)
In order to develop environmentally friendly conductive polymer composites, polylactic acid (PLA) plasticized with polyethylene glycol (PEG), was compounded with carbon black (CB). It was confirmed that PEG efficiently plasticized the PLA, marked by the decrease in glass transition point of PLA, as the PEG content increased. Electrical surface resistance of PEG plasticized PLA/CB composites was found to shift to lower percolation content, indicating that conductive network of CB is easier to be formed inside plasticized PLA, compared to the neat PLA matrix. Moreover, addition of PEG also helped to increase the elongation of break of the composites.